The São Paulo Declaration (1998): Nothing Dates More Rapidly than the Present - Chris Rojek; Cesar Teixeira Castilho (Universidade Estadual Paulista (UNESP), 2018)
Abstract The Sao Paulo Declaration (1998) committed leisure professionals to extending Rights, Inclusion and Social Order in leisure customs and practice. The engine for this intervention consisted of the twin processes of globalization and cosmopolitanism. Both were seen as dissolving economic and political barriers. The Declaration did not make use of the term 'world society'. On the other hand it clearly defined itself to be part of a global movement that addressed leisure for all. In the last 20 years, the progress made n fulfilling the terms of the Declaration has been disappointing. Economic barriers of wealth inequality and uneven development in globalization and cosmopolitanism have blocked many aspects of the Rights, Inclusion and Order articulated in the Declaration. This paper examines how far globalization and cosmopolitanism have progressed in achieving the principle that 'all persons have the right to leisure.' It examines data on wealth inequality, debt and unemployment rates to consider some of the concrete impediments. It concludes by maintaining that there is a need to go beyond the Sao Paulo Declaration by addressing the economic and political barriers that currently prevent leisure from being a right for all.